Developing a Digital Scales System using Internet of Things Technology on Indonesia Digital Farm - Kusrini Kusrini; Banu Santoso; Eko Pramono; Muhammad Koprawi; Jeki Kuswanto; Elik Hari Muktafin; Ichsan Wasiso (Universitas Negeri Semarang, 2023)
Purpose: This research aims to develop a digital scales system using internet of things technology on Indonesia digital farm.Methods: The stages of the research were carried out starting from literature studies, system requirements analysis, digital scales system design, system testing, and analysis of system test results. This model consists of hardware and software. The hardware consists of sensors for data collection in the field or using cameras, data input devices, data senders to data centers, data centers, and data processors, and data output that can be accessed on a laptop or a smartphone in real-time.Result: The results of the study show that IoT-based digital scales can be used to read goat weighing results based on RFID data input and camera image capture. The average body weight of a goat that has been weighed is 106.5 pounds, while the average body height of a goat is 150.7 cm.Novelty: The IoT-based digital scales system (IoT-DSS) can be used to measure the weight and height of goats so that the weighing process is more efficient.